Collaborative Writing: Fostering Foreign Language and Writing Conventions Development - Elola Idoia; Oskoz, Ana (Language Learning and Technology)
The use of social technologies, such as wikis and chats, has brought a renewed attention to L2 collaborative writing. Yet, a question that still remains to be answered is the extent to which learners’ writing is enhanced when using these tools. By analyzing learners’ individual and collaborative writing, this study (a) explores L2 learners’ approaches to the writing task in the wikis, (b) examines learners’ collaborative synchronous interactions when discussing content, structure and other aspects related to the elaboration of the writing task, and (c) describes learners’ perceptions of individual and collaborative writing and their impressions of the use of social tools in the FL writing class. Analysis of the data showed that while statistically significant differences were not evident in terms of fluency, accuracy and complexity when comparing the individual and collaborative assignments, there were observable trends that inform us about how learners’ interactions with the text differ when working individually or collaboratively. Further, an analysis of learners’ approaches to collaborative writing through the use of social tools shows that wikis and chats allowed them to concentrate on writing components in a different, yet complementary, manner depending on whether they interacted in the wikis or in the chats.